Benthic Hydrozoans as Potential Indicators of Water Masses and Anthropogenic Impact in the Sea of Marmara - TOPÇU, NUR EDA; MARTELL, LUIS FELIPE; YILMAZ, IZZET NOYAN; ISINIBILIR, MELEK (Mediterranean Marine Science, 2018)
Changes in the abundance and distribution of marine benthic hydrozoan species are indicative of variations in environmental conditions in the marine realm. The comparative analysis of such assemblages can improve our understanding of environmental and ecological conditions in the Sea of Marmara, a strongly stratified and heavily populated inland sea connecting the Aegean and Black seas, on route of national and international maritime traffic. We compared the hydrozoan assemblages occurring in harbours with those developed at natural sites, as well as the assemblages associated with the Black Sea water mass versus the Mediterranean water mass in the vicinities of the Prince Islands, the north-easternmost section of the Sea of Marmara. Sampling took place at 12 stations, once in March 2015 and once in August 2015 in order to cover species with both warm and cold water affinities. Multivariate analyses showed that benthic hydroid assemblages with both affinities differed significantly between the heavily trafficked harbours of the Prince Islands (connected to the metropolis of Istanbul) and areas without human settlements and maritime traffic. In addition, highly distinct hydroid assemblages were found characterizing both areas with water of Mediterranean origin and areas with water from Black Sea origin. Based on our results, we discuss the potential for the use of these organisms as indicators of water masses and anthropogenic impact at the regional level.